2023
DOI: 10.3390/jcm12062390
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Periprocedural and Intermediate-Term Outcomes of TAVI in Patients with Ejection Fraction ≤ 20% vs. Patients with 20% < EF ≤ 40%

Abstract: Treatment of congestive heart failure (CHF) with left ventricular (LV) systolic dysfunction and severe aortic stenosis (AS) is challenging, yet transcatheter aortic valve replacement (TAVR) has emerged as a suitable treatment option in such patients. We compared the periprocedural outcomes of TAVR in patients with an ejection fraction (EF) of ≤20% (VLEF group) to patients with an EF > 20% to ≤40% (LEF group). We included patients with severe AS and reduced LV ejection fraction (LVEF ≤ 40%) who underwent TAV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Our study also demonstrated an increased incidence of planned heart-lung circulatory support in patients with a reduced ejection fraction (6.1% vs. 2.5%, p = 0.035). Consistent with other research, individuals with a low EF were found to require mechanical support more frequently, such as intra-aortal balloon pump or ECMO [11]. These insights suggest that offering prepared support may be beneficial to ensure a secure valve implantation for these patients.…”
Section: Discussionsupporting
confidence: 84%
“…Our study also demonstrated an increased incidence of planned heart-lung circulatory support in patients with a reduced ejection fraction (6.1% vs. 2.5%, p = 0.035). Consistent with other research, individuals with a low EF were found to require mechanical support more frequently, such as intra-aortal balloon pump or ECMO [11]. These insights suggest that offering prepared support may be beneficial to ensure a secure valve implantation for these patients.…”
Section: Discussionsupporting
confidence: 84%